2019
DOI: 10.1038/s41467-019-10443-2
|View full text |Cite
|
Sign up to set email alerts
|

Loci for human leukocyte telomere length in the Singaporean Chinese population and trans-ethnic genetic studies

Abstract: Genetic factors underlying leukocyte telomere length (LTL) may provide insights into telomere homeostasis, with direct links to disease susceptibility. Genetic evaluation of 23,096 Singaporean Chinese samples identifies 10 genome-wide loci ( P < 5 × 10 −8 ). Several of these contain candidate genes ( TINF2 , PARP1 , TERF1 , ATM and POT1 ) with potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 66 publications
7
100
1
Order By: Relevance
“…These six SNPs exhibit strong linkage disequilibrium (LD) (R 2 > 0.71) with rs2251795 in JPT. This result is concordant with the previous studies that indicated the association of rs2293607 (T allele) and rs10936599 (C allele) (absolute linkage equilibrium with T allele of rs2251795 in JPT) with longer leukocyte telomere length 30,43 . On the other hand, the previous study reported that the risk allele of rs2736100 on TERT (5p15.33) was associated with shorter telomere length, while TERC loci (rs10936600 on 3q26.2) was not associated with telomere length in leiomyoma tissues 15 .…”
Section: Discussionsupporting
confidence: 93%
“…These six SNPs exhibit strong linkage disequilibrium (LD) (R 2 > 0.71) with rs2251795 in JPT. This result is concordant with the previous studies that indicated the association of rs2293607 (T allele) and rs10936599 (C allele) (absolute linkage equilibrium with T allele of rs2251795 in JPT) with longer leukocyte telomere length 30,43 . On the other hand, the previous study reported that the risk allele of rs2736100 on TERT (5p15.33) was associated with shorter telomere length, while TERC loci (rs10936600 on 3q26.2) was not associated with telomere length in leiomyoma tissues 15 .…”
Section: Discussionsupporting
confidence: 93%
“…The LTL for each sample was measured in duplicates and the average T/S ratio was used for subsequent analysis. Detailed description for LTL measurement in SCHS, including standard curve generation, PCR condition and coefficients of variation was published previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genetic studies have identified several loci associated with leukocyte telomere length (LTL) [ 17 , 18 ]. However, the contribution of these variants, even in combination, to the overall heritability of LTL is modest.…”
Section: Introductionmentioning
confidence: 99%
“…Some types of cancer are positively associated with telomere length. A number of groups such as the Telomeres Mendelian Randomization Collaboration [ 126 ] have analyzed genomic variants associated with telomere length at various loci, including POT1 [ 127 ], and have reported causal relationships between longer telomeres and the risk of cancers, including the following: melanoma, glioma, non-small-cell lung, serous ovarian, bladder, testicular germ cell, renal and endometrial [ 126 ]. It is interesting to speculate that this may because long telomeres allow a larger number of cell divisions while pro-oncogenic mutations are accumulating in nascent tumor cells, and that mutations in POT1 may also have the effect of increasing telomere length in telomerase-positive tissue stem cells through a decreased ability of the mutant POT1 protein to inhibit telomerase activity.…”
Section: Potential Mechanisms Of the Contribution Of Pot1 Dysfunctmentioning
confidence: 99%